2003
DOI: 10.1074/jbc.m213088200
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin 1A Binds to the Cytoplasmic C Terminus of Kv2.1 to Regulate Channel Gating and Trafficking

Abstract: Voltage-gated K؉ (Kv) 2.1 is the dominant Kv channel that controls membrane repolarization in rat islet ␤-cells and downstream insulin exocytosis. We recently showed that exocytotic SNARE protein SNAP-25 directly binds and modulates rat islet ␤-cell Kv 2.1 channel protein at the cytoplasmic N terminus. We now show that SNARE protein syntaxin 1A (Syn-1A) binds and modulates rat islet ␤-cell Kv2.1 at its cytoplasmic C terminus (Kv2.1C). In HEK293 cells overexpressing Kv2.1, we observed identical effects of chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
135
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(145 citation statements)
references
References 26 publications
(49 reference statements)
7
135
3
Order By: Relevance
“…Previous work had shown that these t-SNAREs can bind to and regulate the gating of Kv2.1. [15][16][17][18] However, since the gating of the delayed rectifier does not change with apoptosis, 2 the neurotoxin results, in concert with our trafficking experiments, are most consistent with the requirement of t-SNARE proteins for the membrane fusion required for insertion of new channels into the cell surface. This conclusion also is in accordance with the observations that overexpression of syntaxin in cell lines inhibits exocytosis 19 and Kv2.1 surface expression.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous work had shown that these t-SNAREs can bind to and regulate the gating of Kv2.1. [15][16][17][18] However, since the gating of the delayed rectifier does not change with apoptosis, 2 the neurotoxin results, in concert with our trafficking experiments, are most consistent with the requirement of t-SNARE proteins for the membrane fusion required for insertion of new channels into the cell surface. This conclusion also is in accordance with the observations that overexpression of syntaxin in cell lines inhibits exocytosis 19 and Kv2.1 surface expression.…”
Section: Discussionsupporting
confidence: 79%
“…This conclusion also is in accordance with the observations that overexpression of syntaxin in cell lines inhibits exocytosis 19 and Kv2.1 surface expression. 16 Of interest, t-SNARE proteins have also been implicated in the trafficking and/or surface expression of other plasma membrane channels, Figure 4 Surface delivery of Kv2.1(I376C) in cortical neurons during apoptosis. (a) Whole-cell K þ currents from Kv2.1(I379C)-expressing control (CON) cortical neurons or neurons triggered to undergo apoptosis (AP) by 100 mM DTDP (10 min).…”
Section: Discussionmentioning
confidence: 99%
“…In these experiments, we also confirmed the described association of syntaxin and Kv2.1 (Fig. 3A) (47)(48)(49). The increased CaMKII signal in Kv2.1-expressing cells could be the result of a direct interaction of the kinase with the K + channel.…”
Section: Injurious Oxidant Exposure Leads To Camkii Activation In Neusupporting
confidence: 75%
“…CaMKII has been shown to regulate exocytosis via a specific interaction with syntaxin (43)(44)(45)(46). In addition, syntaxin is known to bind to the most proximal region of the Kv2.1 C terminus, termed C1a, during Ca 2+ -facilitated exocytosis in pancreatic and other nonneuronal cells (47)(48)(49). Importantly, we showed that syntaxin is also required for the membrane insertion of Kv2.1 channels during apoptosis (23).…”
Section: Injurious Oxidant Exposure Leads To Camkii Activation In Neumentioning
confidence: 66%
“…Syx and SNAP Directly Bind Cytosolic Domains of Kv2.1-Previously, we have shown in an in vitro binding assay that Syx and SNAP bind to the Kv2.1 channel (14,28). In this study we carried out a more comprehensive in vitro binding assay to substantiate the physical interaction of the channel with these proteins.…”
Section: Resultsmentioning
confidence: 99%